Good Morning, Midnight - Brooks-Dalton, Lily, 1987- (New York : Random House, 2016)
After a catastrophic event silences Mission Control communications, an astronaut returning from a mission to Jupiter and an aging scientist at a remote Arctic outpost are haunted by love, memory, and regret as the world confronts an uncertain future.
Keywords: Astronauts -- Fiction; Science fiction